Banks, Firms, and Jobs - Berton, Fabio (IMF Working Papers; Working Paper ;, 2017)
We analyze the employment effects of financial shocks using a rich data set of job contracts, matched with the universe of firms and their lending banks in one Italian region. To isolate the effect of the financial shock we construct a firm-specific time-varying measure of credit supply. The contraction in credit supply explains one fourth of the reduction in employment. This result is concentrated in more levered and less productive firms. Also, the relatively less educated and less skilled workers with temporary contracts are the most affected. Our results are consistent with the cleansing role of financial shocks.